Current status and research progress of minimally invasive treatment of glioma - Wu, Hao; Zhou, Feng; Gao, Wenwen; Chen, Peng; Wei, Yao; Wang, Fenglu; Zhao, Haikang (Frontiers in Oncology, 2024)
Glioma has a high malignant degree and poor prognosis, which seriously affects the prognosis and quality of life of patients. Traditional treatment methods mainly include craniotomy tumor resection, postoperative radiotherapy and chemotherapy. Although these methods have achieved remarkable results, they still have certain limitations and adverse reactions. With the introduction of the concept of minimally invasive surgery and its clinical application as well as the development and progress of imaging technology, minimally invasive treatment of glioma has become a research hotspot in the field of neuromedicine, including photothermal treatment of tumor, photodynamic therapy, laser interstitial hyperthermia of tumor and electric field therapy of tumor. These therapeutic methods have the advantages of precision, small trauma, quick recovery and remarkable curative effect, and have been widely used in clinical practice. The purpose of this review is to introduce the progress of minimally invasive treatment of glioma in recent years and the achievements and prospects for the future